Barbados Low Dose Aspirin Study in Pregnancy (BLASP): a randomised trial for the prevention of pre-eclampsia and its complications. - Rotchell, Y; Cruickshank, J; Gay, M; Griffiths, J; Stewart, A; Farrell, B; Ayers, S; Hennis, A; Grant, A; Duley, L; Collins, R (1998)
OBJECTIVE: To determine whether prophylactic, low dose controlled-release aspirin improves outcome for pregnant women and their babies in Barbados. DESIGN: Randomised placebo-controlled trial. SETTING: The Queen Elizabeth Hospital, Barbados. POPULATION: All women attending antenatal clinics between 12 and 32 weeks of gestation were eligible, if without specific contraindications to aspirin and unlikely to deliver immediately. METHODS: Randomisation was computer-generated in the antenatal clinic; 1822 women were allocated to receive 75 mg controlled-release aspirin and 1825 matching placebo. MAIN OUTCOME MEASURES: Proteinuric pre-eclampsia, other pregnancy-induced hypertension, pregnancy duration, birthweight, stillbirths and neonatal deaths, major neonatal events. RESULTS: All but three women from each group were followed up successfully. Forty-four percent were primigravid, and 8% had previous obstetric complications. There were no significant differences between the allocated treatment groups in the incidence of proteinuric pre-eclampsia (40 [2.2%] of those allocated aspirin, compared with 46 [2.5%] allocated placebo), of preterm delivery (255 [14.0%] vs 270 [14.8%]), of birthweight < 1500 g (32 [1.7%] vs 33 [1.8%]) or of stillbirth and neonatal death (44 [2.4%] vs 38 [2.1%]). Aspirin was not associated with excess risk of maternal or fetal bleeding. CONCLUSIONS: The results of this study in Barbados do not support the routine use of low dose aspirin for prevention of pre-eclampsia or its complications, confirming results of previous large trials in other settings.